Calcium signalling through L‐type calcium channels: role in pathophysiology of spinal nociceptive transmission. (24th March 2017) - Roca‐Lapirot, Olivier; Radwani, Houda; Aby, Franck; Nagy, Frédéric; Landry, Marc; Fossat, Pascal
Abstract : L‐type voltage‐gated calcium channels are ubiquitous channels in the CNS. L‐type calcium channels (LTCs) are mostly post‐synaptic channels regulating neuronal firing and gene expression. They play a role in important physio‐pathological processes such as learning and memory, Parkinson's disease, autism and, as recognized more recently, in the pathophysiology of pain processes. Classically, the fundamental role of these channels in cardiovascular functions has limited the use of classical molecules to treat LTC‐dependent disorders. However, when applied locally in the dorsal horn of the spinal cord, the three families of LTC pharmacological blockers – dihydropyridines (nifedipine), phenylalkylamines (verapamil) and benzothiazepines (diltiazem) – proved effective in altering short‐term sensitization to pain, inflammation‐induced hyperexcitability and neuropathy‐induced allodynia. Two subtypes of LTCs, Cav 1.2 and Cav 1.3, are expressed in the dorsal horn of the spinal cord, where Cav 1.2 channels are localized mostly in the soma and proximal dendritic shafts, and Cav 1.3 channels are more distally located in the somato‐dendritic compartment. Together with their different kinetics and pharmacological properties, this spatial distribution contributes to their separate roles in shaping short‐ and long‐term sensitization to pain. Cav 1.3 channels sustain the expression of plateau potentials, an input/output amplification phenomenon that contributes to short‐term sensitization to pain such as prolonged after‐discharges, dynamic receptive fields and windup. The Cav 1.2 channels support calcium influx that is crucial for the excitation‐transcription coupling underlying nerve injury‐induced dorsal horn hyperexcitability. These subtype‐specific cellular mechanisms may have different consequences in the development and/or the maintenance of pathological pain. Recent progress in developing more specific compounds for each subunit will offer new opportunities to modulate LTCs for the treatment of pathological pain with reduced side‐effects. Linked Articles: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc